2022
DOI: 10.3390/molecules27113396
|View full text |Cite
|
Sign up to set email alerts
|

The Modulation of Arachidonic Acid Metabolism and Blood Pressure-Lowering Effect of Honokiol in Spontaneously Hypertensive Rats

Abstract: Background: Cardiovascular diseases have consistently been the leading cause of death in the United States over the last two decades, with 30% of the adult American population having hypertension. The metabolites of arachidonic acid (AA) in the kidney play an important role in blood pressure regulation. The present study investigates the antihypertensive effect of honokiol (HON), a naturally occurring polyphenol, and examines its correlation to the modulation of AA metabolism. Methods: Spontaneously hypertensi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 26 publications
(37 reference statements)
0
6
0
Order By: Relevance
“…Recently, the inhibition of sEH and increased bioavailability of EETs have been proposed as promising approaches for the prevention and treatment of hypertension. Our research and others have shown that the sub-chronic inhibition of sEH for 1–6 weeks lowers blood pressure and ameliorates the organ damage associated with hypertension [ 7 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 54%
See 4 more Smart Citations
“…Recently, the inhibition of sEH and increased bioavailability of EETs have been proposed as promising approaches for the prevention and treatment of hypertension. Our research and others have shown that the sub-chronic inhibition of sEH for 1–6 weeks lowers blood pressure and ameliorates the organ damage associated with hypertension [ 7 , 10 , 11 , 12 ].…”
Section: Introductionmentioning
confidence: 54%
“…Our laboratory has been interested in the past two decades in understanding the health benefits of small natural molecules [ 7 , 12 , 13 , 16 , 19 , 20 ]. Catechin (CAT) is among the most abundant and commonly studied flavonoid that exists in a wide variety of foods and herbs.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations